Problems of Arabic Speaking Skills at the Darul Muttaqin Nahdlatul Wathan Diniyah Islamiyah Perian Modern Islamic Boarding School - Muhammad Hamdani; Kamariah Kamariah; Mahsur Mahsur; Ruwaida Ruwaida (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study is to investigate and analyze the problems associated with the development of Arabic speaking skills among the students of Pondok Pesantren Darul Muttaqin NWDI Perian, which uses a qualitative approach in the research methodology. With this approach, the research seeks to explore these issues through verbal analysis without utilizing statistical techniques. Primary and secondary data were collected through a series of careful observations, interviews, and documentation. The findings of this study highlight the complexity of the challenges in developing Arabic speaking skills in a pesantren environment. The study identified two main aspects of problematic speaking skills, namely linguistic and non-linguistic aspects. The linguistic aspect includes rigidity and obstacles in Arabic speaking fluency among students, while the non-linguistic aspect involves factors such as lack of motivation from teachers, the tendency to use Indonesian in daily communication, and learning patterns that tend to be monotonous. Through this research, it is hoped that a deeper understanding of the challenges in developing Arabic speaking skills in pesantren will be achieved. The practical implications of this study include the importance of improving learning strategies that focus on improving speaking skills, as well as the need for higher motivation for teachers to face this challenge. This research is expected to make a valuable contribution to curriculum development and more effective learning strategies in Islamic educational institutions.